The Governance of Non-Cash Food Assistance Provision in Enhancing the Well-being of the Community in the City of Baubau - La Didi; Asmiddin Asmiddin (UIN Sunan Gunung Djati, 2023)
The provision of non-cash food assistance in Baubau City has faced critical challenges due to mismanagement, resulting in eligible individuals not receiving their entitled benefits and the failure of the assistance program to effectively enhance the community's welfare. These issues can be primarily attributed to poor governance practices. In this study, we aim to investigate the governance of non-cash food assistance in Baubau City, focusing on three key dimensions: accountability, transparency, and community participation. Using a qualitative descriptive approach, data was collected through interviews with relevant stakeholders, selected through purposive sampling, as well as observations of beneficiary community groups and an analysis of program documents related to non-cash food assistance. The research findings highlight significant shortcomings in the governance of the program, particularly in terms of accountability, transparency, and community engagement. These issues underscore the urgent need for improved governance practices to ensure that non-cash food assistance effectively contributes to the prosperity and self-sufficiency of the communities it serves.